2011
DOI: 10.1007/s13312-011-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Rescue high frequency oscillation in neonates with acute respiratory failure

Abstract: The aim was to study the efficacy of rescue High Frequency Oscillatory Ventilation (HFOV) in improving the oxygenation and ventilation in neonates with acute respiratory failure after failing Conventional Mechanical Ventilation (CMV). Primary outcome was short term oxygenation, lung recruitment, and ventilation and secondary outcome studied was survival. 675 babies were ventilated and 97 of them received HFOV. HFOV significantly improved oxygenation index, alveolar-arterial oxygen gradient, pH, PCO2, PO2 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 10 publications
5
25
3
Order By: Relevance
“…Similar improvement of arterial alveolar oxygen gradient was seen by Poddutoor KP et al and Kyung lee et al at 6hrs respectively in their studies. [14,15,16]. Jaballah et al, found improvement in OI after 1 hr of HFOV in neonates treated with respiratory failure while our study results were similar to response in Sainaik et al, and Kyung lee et al, where 6 hours after institution of HFOV, OI improvement was seen [14,17,18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar improvement of arterial alveolar oxygen gradient was seen by Poddutoor KP et al and Kyung lee et al at 6hrs respectively in their studies. [14,15,16]. Jaballah et al, found improvement in OI after 1 hr of HFOV in neonates treated with respiratory failure while our study results were similar to response in Sainaik et al, and Kyung lee et al, where 6 hours after institution of HFOV, OI improvement was seen [14,17,18].…”
Section: Discussionsupporting
confidence: 85%
“…Poddutoor KP et al study showed fifty seven babies (58.77%) survival and high mortality in < 28 weeks neonates, especially babies with pulmonary hemorrhage, sepsis and CDH [16]. Pulmonary hemorrhage, sepsis were also common primary diagnosis in this study that affected the outcome and mortality.…”
Section: Discussionsupporting
confidence: 51%
“…In another study, Sun et al (2014) showed that initial ventilation with high frequency ventilation in preterm infants with severe respiratory distress syndrome reduced the incidence of death and borderline personality disorder, and improved long-term neurodevelopment outcomes. In neonates with acute lung injury, rescue high frequency ventilation significantly improved oxygenation index, alveolar-arterial oxygen gradient, pH, PCO 2 , and PO 2 and caused a better lung recruitment within 2 h (Poddutoor et al 2011). In neonates treated for acute respiratory failure, significant decreases in mean airway pressure, FiO 2 , and oxygenation index were found after starting high frequency ventilation, and PaCO 2 decreased after a further hour of ventilation (Jaballah et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…6 However, None of the parameters was statistically significant; PROM, premature rupture of membranes; * median (range) documented studies of HFOV from India are sparse as it is only employed as a rescue mode. [9][10][11] This is the first Indian study to investigate early HFOV as a primary mode of ventilation in preterm infants. Because conventional mechanical ventilation is usually the routine mode of ventilation, clinical teams often have less experience of HFOV, especially in resource-poor settings.…”
Section: Discussionmentioning
confidence: 99%
“…6 Currently, HFOV in neonates is used only as a rescue mode of ventilation in a few Indian centres. [9][10][11] We have demonstrated that elective HFOV in preterm infants is feasible in developing countries in centres with experience of its use. In such settings, therefore, it can be considered a viable option for early ventilation of preterm neonates.…”
Section: Discussionmentioning
confidence: 99%